Writing Spaces at Oklahoma State University - Driscoll, Dana; Daniel, Joshua; Stewart, Mary K.; Vetter, Matthew; Daniels-Lerberg, Trace; Garcia-Boswell, Victoria (Open textbook library., 2023)
This resource focuses on the various processes involved in researching answers to various inquiry questions and building effective arguments within and outside academic contexts. The curriculum takes students through the processes of listening/summarizing, asking questions, characterizing scholarly debates, and entering those debates in order to meaningfully contribute to ongoing conversations.